2020
DOI: 10.7150/thno.33482
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicle-mediated delivery of miR-101 inhibits lung metastasis in osteosarcoma

Abstract: Rationale: Extracellular vesicles (EVs) have emerged as novel mediators of cell-to-cell communication that are capable of the stable transfer of therapeutic microRNAs (miRNAs), and thus, EVs hold immense promise as a miRNA delivery system for cancer therapy. Additionally, as miRNA-containing EVs are secreted into circulation, miRNAs contained within plasma EVs may represent ideal biomarkers for diseases. The objective of this study was to characterize a potential tumor suppressor miRNA, miR-101, and explore th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(98 citation statements)
references
References 54 publications
0
98
0
Order By: Relevance
“…57 Similar studies emerged, by using lentiviral vector transfected into the donor cells as well, Zhang et al prepared miR-101 packaging EVs, which were able to inhibit osteosarcoma cell invasion and migration in vitro as well as inhibited osteosarcoma metastasis in vivo. 58 In addition to delivery of nucleic acid directly, EVs were employed as an advanced tool for genomic editing. CRISPR-Cas9 is a novel implement to accurately incise DNA sequences with the aid of a single guide RNA (sgRNA), which is complementary to the target gene.…”
Section: Delivery Of Nucleic Acid Cargo By Evsmentioning
confidence: 99%
“…57 Similar studies emerged, by using lentiviral vector transfected into the donor cells as well, Zhang et al prepared miR-101 packaging EVs, which were able to inhibit osteosarcoma cell invasion and migration in vitro as well as inhibited osteosarcoma metastasis in vivo. 58 In addition to delivery of nucleic acid directly, EVs were employed as an advanced tool for genomic editing. CRISPR-Cas9 is a novel implement to accurately incise DNA sequences with the aid of a single guide RNA (sgRNA), which is complementary to the target gene.…”
Section: Delivery Of Nucleic Acid Cargo By Evsmentioning
confidence: 99%
“…First, in vitro testing showed that miR-101, delivered via exosomes, reduced the invasion and migration of the tested osteosarcoma cell line. Then, the lung metastasis animal model of osteosarcoma showed that the systemic administration of the miR-101-enriched-exosomes suppressed lung metastasis with no apparent side effects [ 90 ].…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…In patients with malignant pleural mesothelioma, TargomiRs, a miR-16 mimic, showed an acceptable safety profile and signs of activity [100] . Scientists have also developed nanoparticles, bioengineered prodrugs and EVs to deliver miRNA mimics (miR-199a-3p, let-7a, miR-34a, miR-145, miR-143, and miR-101) to OS cells in vitro and in vivo ( Table 2 ) [101] , [102] , [103] , [104] , [105] .…”
Section: Mirna Dysregulation In Osmentioning
confidence: 99%